Bilateral Interaction between Mainland China and Hong Kong Audiovisual Products under the Perspective of Cross-cultural Communication - Zhou, Zhengyi; Zheng, Liuyi; Qi, Yuxi (Journal of Modern Social Sciences, 2025)
At the present time, the dissemination of media represents one of the most significant methods of facilitating communication between disparate locations. The dissemination of cultural and creative products expressed in audiovisual formats facilitates cross-regional communication, thereby reinforcing the common culture within the group. Hong Kong, China and Mainland China represent distinct regions of the Han Chinese Cultural Circle. They not only reflect the cultural attractions within this cultural circle through a variety of media communication, but also respond to external cultural influences in the context of globalization. The latest figures indicate that Mainland China represents the largest outlet for Hong Kong’s audio-visual products. However, the dissemination effect of Mainland products in Hong Kong is generally less pronounced than that of products from the United States and Japan. In particular, the United States has utilized the brand name of Hollywood films to disseminate its culture and values on a global scale through cross-cultural communication. While the shared culture provides audiovisual products with a lasting communication advantage in both Hong Kong and the Mainland, it can also be used at a later stage to further promote in-depth cultural exchanges and dissemination between the two places through policies, cooperation and cultural adaptations. However, this approach also faces challenges, including the USA’s cultural leadership within traditional cultural circles.